The intriguing question of regional and territorial development in rural areas: analytical variations and Public Policy - Frederic Wallet; Andre Torre (European Regional Science Association (ERSA), 2011)
The aim of this paper is to shed light on territorial development and rural development issues, and to review the links and differences between. Indeed, everything points to reach those dimensions that have long seemed disconnected. On the one hand, rural policies incorporate explicitly the territorial dimension, even though the rural-urban distinction is increasingly blurred. At the same time, decentralization, subsidiarity, the regionalization of agricultural production, but also short circuits or local foods deal with the generalization of an urban model. Finally, regional science pays attention to agricultural and rural dimensions, even though research on rural areas is opening to territorial issues. The first part of the paper is devoted to a presentation and a critical attempt to define the concepts of development, territory and rural. The second part addresses the issues of regional and territorial development with a presentation of the major theories and key public policies, and concludes with a reflection on the ways for reconciliation between theory and policy. The third part follows the same pattern applied to the issue of rural development, from theoretical analyses to concrete policies.
Keywords: 330; regional development; territorial development; rural development; rural areas; public policy